USM STRENGTHENS STRATEGIC COOPERATION WITH TELKOM UNIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 5 June 2015 Universiti Sains Malaysia (USM) through its Graduate School of Business (GSB) continues to strengthen its strategic cooperation with Telkom University (TelU), Bandung, Indonesia by signing a Memorandum of Understanding (MoU) held at GSB Meeting Room today.